Research on the accelerating effect and driving mechanism of the African swine fever epidemic on the capitalization of hog farming: evidence from China - Hua, Junguo; Tian, Meng; Jia, Yunfei; Chen, Yufan (Frontiers in Veterinary Science, 2025)
IntroductionThe outbreak of African swine fever (ASF) has led to a sharp increase in the price of hogs, accelerating the capitalization process of the hog industry and causing China’s hog industry to enter a “super hog cycle,” which has attracted much attention.MethodsBased on this, to clarify the mechanism of ASF on the capitalization of hog farming and enrich the relevant theoretical research, this paper uses panel data from 30 provinces in China from 2013 to 2023, and adopts the difference-in-differences model (DID) and the moderation effect model to analyze the impact of the epidemic outbreak on the capitalization of pig farming, providing a new perspective for exploring the influencing factors of hog farming capitalization.Results and discussionThe research found that ASF significantly accelerated the capitalization process of hog farming. This conclusion remained valid after undergoing a series of robustness tests. Moreover, the improvement of industrial agglomeration degree and the strengthening of government support would have a significant positive regulatory effect on it. Heterogeneity analysis revealed that in regions with high agricultural capital stock and non-feed-producing areas, the positive impact of ASF on the capitalization process of hog farming was more significant. Based on this, the article proposed policy suggestions such as strengthening the epidemic prevention and control system, preventing excessive expansion of hog production capacity, coordinating efforts through multiple channels to enhance the capitalization level of the hog industry, and promoting the high-quality development of the hog industry.